PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI BILANGAN BULAT - Tiroida Harahap; Agus Makmur; Wirna Arifitriana (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
Research shows that the results of the student's math problem solving skills test by applying the Cooperative Type Think-Pair-Share learning model in cycle I obtained a percentage of 70% with the criterion